Combination of Selective Water Excitation and Magnetization Transfer on T1-FFE Sequence Shoulder Joint MRI Comparative Study with T1-SPIR Sequence as an Alternative to Increase Anatomical and Pathological Information of Muscles - I Putu Eka Juliantara (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Constraints which arise in the examination of shoulder joint MRI when general practitioner and radiologists need an informative image of muscle without meaningful contributions from fat signal around the tissues. The routine protocol used was not able to accommodate this issue, consequently, the muscle image in the routine sequence clearly also experiences signal suppression. The combination of Selective Water Excitation (SWE) and Magnetization Transfer (MT) techniques in 3D-FFE applied to be able to display muscle images better by applying selective pulses and chemical changes in the shoulder joint tissue. This study was a comparative analytic study with a quasi-experimental one group post-test only design which aims to determine the effect of SWE and MT as an alternative to improving the image information of T1 FFE sequence shoulder MRI images compared to T1 SPIR sequences. By applying purposive-convenience sampling with time saturation, this study used 20 shoulder MRI patients and 2 radiologists as respondents for image evaluation. Significant results were shown in the assessment of images information (anatomical and pathological information). All indicators show a P-value of <0,001 (P < ?). T1 FFE-SWEMT sequence showing superiorities in all aspects assessed compared to the T1-SPIR sequence. There is a significant effect of combination of SWE and MT techniques to improve images information of shoulder joint MRI when compared with T1-SPIR sequences.